2021
DOI: 10.1177/21501327211053750
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PHQ-9 and PHQ-2 as Screening Tools for Depression and School Related Stress in Inner City Adolescents

Abstract: Background Major depressive disorder is associated with significant morbidity and mortality in adolescents. Suicide is one of the leading causes of mortality between 15 and 19 years. Both AAP and USPSTF recommend routine depression screening of adolescents. Patient Health Questionnaire-2 (PHQ-2) and Patient Health Questionnaire-9 (PHQ-9) are widely used in primary care practice, however, PHQ-2 does not screen for suicidality. School-related factors are known to affect adolescent mental health. Purpose To compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…The prevalence estimate of 11.5% of adolescents screening positive for depressive symptoms is in line with findings from before the pandemic [ 65 ] and with a recent longitudinal German study [ 59 ]. Nevertheless, other studies have revealed a mixed body of evidence, with some reporting lower rates of depressive symptoms in adolescents during the pandemic [ 60 ] and others reporting an increase in depressive symptoms [ 66 ].…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence estimate of 11.5% of adolescents screening positive for depressive symptoms is in line with findings from before the pandemic [ 65 ] and with a recent longitudinal German study [ 59 ]. Nevertheless, other studies have revealed a mixed body of evidence, with some reporting lower rates of depressive symptoms in adolescents during the pandemic [ 60 ] and others reporting an increase in depressive symptoms [ 66 ].…”
Section: Discussionsupporting
confidence: 87%
“…In fact, in severe situations, it can lead to suicidal behavior. 6 , 7 In addition, depressive symptoms in the adult population have been associated mostly with emotional and physical problems. For example, there is evidence of association with anxiety, 8 hopelessness, 9 obesity, 10 cancer, 11 cardiovascular diseases, type 2 diabetes, 12 and visual impairments.…”
Section: Introductionmentioning
confidence: 99%
“…That study found that the yield of both questionnaires remained stable over the first 3 months of the testing period. Of note, after the first 3 months, the PHQ-9 average scores increased while average PHQ-2 scores continued to be stable ( 26 ). Partially in contrast with the above-mentioned finding regarding the PHQ-9, in a recent longitudinal study involving a European-wide sample of patients after Traumatic Brain Injury (TBI), the analysis showed high stability of depression scores as measured by the PHQ-9 at 3-, 6-, and 12-months post-TBI assessments ( 27 ).…”
Section: Discussionmentioning
confidence: 99%